2022
DOI: 10.3389/fvets.2022.893721
|View full text |Cite
|
Sign up to set email alerts
|

Farm-Level Risk Factors Associated With Avian Influenza A (H5) and A (H9) Flock-Level Seroprevalence on Commercial Broiler and Layer Chicken Farms in Bangladesh

Abstract: A cross-sectional study was conducted to identify farm-level risk factors associated with avian influenza A H5 and H9 virus exposure on commercial chicken farms in Bangladesh. For broiler farms, both H5 and H9 seropositivity were associated with visits by workers from other commercial chicken farms [odds ratio (OR) for H5 = 15.1, 95% confidence interval (CI): 2.8–80.8; OR for H9 = 50.1, 95% CI: 4.5–552.7], H5 seropositivity was associated with access of backyard ducks (OR = 21.5, 95% CI: 2.3–201.1), and H9 ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Also, in Bangladesh, poultry farming is one of the most significant livestock industry sectors, contributing to the country's economic growth by creating employment opportunities and income for both rural and semi-urban populations [ [9] , [10] , [11] ]. The industry grew 2.5-fold between 1995 and 2017 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in Bangladesh, poultry farming is one of the most significant livestock industry sectors, contributing to the country's economic growth by creating employment opportunities and income for both rural and semi-urban populations [ [9] , [10] , [11] ]. The industry grew 2.5-fold between 1995 and 2017 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facilities for hand washing and foot washing should be available at farms. Further proper disinfection and cleaning of vehicles should be confirmed before their entrance into farms, and vehicles must be parked at a considerable distance of 30 m from the farm 12 . Litter should be cleaned daily, and dead birds should be buried deep to minimize the risk of spreading H5 and H7 11 .…”
Section: Main Textmentioning
confidence: 99%
“…At producers level, however somewhat outdated, the mortality rate was estimated between 4-8% of the total flock (Islam et al, 2014;Ershad et al, 2004). Poultry carcasses may be disposed of through burial, disposed in concrete disposal pits, incineration, composting or dumping (Gupta et al, 2022;Sarker et al, 2009;rimi et al, 2017). Based on the field visit conducted in March 2022 it was observed that FLW in the informal channel at wet markets (wholesale butchers and retail butchers) was limited, as the butchers slaughter the broilers based on the consumer demand.…”
Section: Chickenmentioning
confidence: 99%